The context in conditional cash transfer (CCT) programs: A royal road to health service utilization to the poor? - Massami Denis Rukiko; Adam Ben Swebe Mwakalobo; Joel Johnson Mmasa (Cogent Business & Management, 2023)
This study addresses the challenges facing Conditional Cash Transfer Programs (CCT) by investigating whether recipients are satisfied with health services and how contextual factors affect the utilization of health services. The study used binary logistic regression to determine households' satisfaction with health facility services and was guided by the theory of change and expectation disconfirmation theory, with independent variables being the contextual factors. Generally, 68.66% of health facility service recipients are satisfied, compared to 31.34% who are not. At 95% confidence interval, an increase in household head education and household members is likely to increase satisfaction with health facility services, while service delays and beliefs in traditional medications are likely to negatively affect satisfaction to around 30% or more. The study calls for constant and continual collaboration between CCT program designers and implementers and health facility service providers, who have a significant role to play in reducing service delays. Moreover, it emphasizes the necessity for contextual factors to be considered in promoting health utilization, which is at the heart of CCT program health conditionality compliance. The study's outcome highlights the need for additional efforts to be focused on the design and implementation of the CCT program, particularly in improving contextual factors, which are often given less attention.
Keywords: 650; cash transfer; Context; health utilization; poverty reduction; TASAF